2003
DOI: 10.1016/s0092-8674(03)00163-6
|View full text |Cite
|
Sign up to set email alerts
|

Migfilin and Mig-2 Link Focal Adhesions to Filamin and the Actin Cytoskeleton and Function in Cell Shape Modulation

Abstract: Cell-extracellular matrix adhesion is an important determinant of cell morphology. We show here that migfilin, a LIM-containing protein, localizes to cell-matrix adhesions, associates with actin filaments, and is essential for cell shape modulation. Migfilin interacts with the cell-matrix adhesion protein Mig-2 (mitogen inducible gene-2), a mammalian homolog of UNC-112, and the actin binding protein filamin through its C- and N-terminal domains, respectively. Loss of Mig-2 or migfilin impairs cell shape modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
446
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 331 publications
(463 citation statements)
references
References 51 publications
14
446
1
2
Order By: Relevance
“…This finding, together with the previous demonstration that MIG2 is localized to focal adhesions and plays a role in controlling actin cytoskeleton dynamics (15), prompted us to investigate the role of MIG2 in TMX2-28 cell invasion. Using transient transfection of siRNAs targeting MIG2, we silenced MIG2 expression by 52% relative to the negative control (siRNAs targeting glyceraldehyde-3-phosphate dehydrogenase, GAPDH; Fig.…”
Section: Mig2 and Cell Invasion By Tmx2-28 Cellsmentioning
confidence: 83%
See 4 more Smart Citations
“…This finding, together with the previous demonstration that MIG2 is localized to focal adhesions and plays a role in controlling actin cytoskeleton dynamics (15), prompted us to investigate the role of MIG2 in TMX2-28 cell invasion. Using transient transfection of siRNAs targeting MIG2, we silenced MIG2 expression by 52% relative to the negative control (siRNAs targeting glyceraldehyde-3-phosphate dehydrogenase, GAPDH; Fig.…”
Section: Mig2 and Cell Invasion By Tmx2-28 Cellsmentioning
confidence: 83%
“…19), we identified several cell membrane, adhesion, and cell-ECMassociated genes that were up-regulated in TMX2-28 cells (Table 1). MIG2 is localized to focal adhesions and plays a role in controlling actin cytoskeleton dynamics (15); therefore, it is probable that MIG2 plays a role in promoting cell motility and invasion. Tu and colleagues (15) examined the expression of MIG2 in a variety of cell types and found that MIG2 was at a relatively low level in MCF-7 cells.…”
Section: Mig2 Expression In Breast Cancer Cell Linesmentioning
confidence: 99%
See 3 more Smart Citations